Remodeling Capacity of Femoral Bone Defect by POP-CHA Bone Substitute: A Study in Rats’ Osteoclast (First Series of POP-based Bone Graft Improvement) - Steven Kumar; Anne Handrini Dewi; Dyah Listyarifah; Ika Dewi Ana (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2011)
Reconstruction of large bone defects caused by trauma, excision of tumors, and congenital malformations can be very difficult to perform. Bone engineering offers an option to improve bone reconstruction procedures. This interdisciplinary field applies the principles of biology and engineering to the development of functional substitutes for damaged bone. Our research aimed to find the ideal scaffold for bone regeneration, focusing on Calcium and Phosphate combination. In this study, Plaster of Paris (POP) was combined with CHA and implanted in femoral condyles of rats. According to the experimental result, it can be concluded that there was no significant difference in response to the implantation of POP and POP-CHA in Sprague Dawley rat femur condyle (p<0.05). It can be stated that both POP-CHA and POP shows similar trait in bone healing.